TGF-β3 Induces Autophagic Activity by Increasing ROS Generation in a NOX4-Dependent Pathway - Yun Zhang; Hong-Mei Tang; Chun-Feng Liu; Xie-Fang Yuan; Xiao-Yun Wang; Ning Ma; Guo-Feng Xu; Song-Ping Wang; Jun Deng; Xing Wang (Hindawi Limited, 2019)
Higher concentrations of reactive oxygen species (ROS) have been associated with epithelial cell damage, cell shedding, and airway hyperresponsiveness. Previous studies have indicated that transforming growth factor-beta (TGF-β) mediates ROS production and NADPH oxidase (NOX) activity. In our previous study, we also observed that TGF-β3 increases mucus secretion in airway epithelial cells in an autophagy-dependent fashion. Although it is well known that the relationship between ROS and autophagy is cell context-dependent, the exact mechanism of action remains unclear. The following study examined whether ROS act as upstream of autophagy activation in response to TGF-β3 induction. Using an allergic inflammation mouse model induced by house dust mite (HDM), we observed elevated lung amounts of TGF-β3 accompanied by increased ROS levels. And we found that ROS levels were elevated and NOX4 expression was increased in TGF-β3-induced epithelial cells, while the lack of NOX4 in the epithelial cells could reduce ROS generation and autophagy-dependent MUC5AC expression treated with TGF-β3. Furthermore, our studies demonstrated that the Smad2/3 pathway was involved in TGF-β3-induced ROS generation by promoting NOX4 expression. The inhibition of ROS generation by N-Acetyl-L-cysteine (NAC) resulted in a decrease in mucus expression and autophagy activity in vivo as well as in vitro. Finally, TGF-β3-neutralizing antibody significantly reduced the ROS generation, mucus expression, and autophagy activity and also decreased the phosphorylation of Smad2 and Smad3. Taken together, the obtained results revealed that persistent TGF-β3 activation increased ROS levels in a NOX4-dependent pathway and subsequently induced autophagy as well as MUC5AC expression in the epithelial cells.